Cognitive evolution of patients with mild Alzheimer's disease can be predicted by circulatory microRNA expression profile: Biomarkers (non‐neuroimaging)/Prognostic utility. (7th December 2020) - Dakterzada, Faride; Piñol, Gerard; Carnes, Anna; Targa, Adriano; Moncusi, Anna; Benitez, Ivan David; Huerto, Raquel; Barbe, Ferran
Abstract: Background: To evaluate whether the expression profile of plasma microRNAs is able to predict the cognitive evolution of patients with early‐phase Alzheimer's disease (AD). Method: Through the Mini‐Mental State Examination (MMSE), we evaluated the cognitive level of 19 AD patients at the baseline and after two years of follow‐up. The patients were grouped according to the rate of decline in the MMSE score along the two years: those who lost less than 4 points (N = 8) and those who lost four or more points (N = 11). To assess the expression profile of circulating microRNAs, blood samples were collected at baseline and plasma was used for total RNA extraction. The extracted RNA was subjected to two 384‐well TaqMan® array cards. Result: We found a profile of 17 microRNAs that were differentially expressed between the two groups. From those, 11 microRNAs had an increased expression in patients with higher cognitive decline while 6 microRNAs had a decreased expression in these patients compared with those with a mild cognitive decline (Image). Furthermore, we observed that a subset of three microRNAs provided a tool with AUC of 0.90 for predicting the severity of the cognitive decline. Conclusion: These preliminary results are indicating that the profile of circulating microRNAs could be a useful tool for predicting the cognitive evolution in patients with early‐stage AD. The results of this study need to be validated in an independent cohort.